DECISION SUPPORT SYSTEM FOR DETERMINING LECTURER CANDIDATES FOR THE POSITION OF HEAD OF WORK UNIT AT KUANTAN SINGINGI ISLAMIC UNIVERSITY USING THE SIMPLE ADDITVE WEIGHTING (SAW) METHOD - Aprizal, Aprizal; Helpi Nopriandi; Erlinda, Erlinda (Sean Institute, 2022)
Kuantan Singingi Islamic University in determining Lecturer candidates as work unit head office holders is carried out by means of Lecturers submitting proposals as self-submission candidates as work unit head candidates. So that from the proposals for submitting these candidates, it is considered by the leadership of the Kuantan Singingi Islamic University for each candidate, which candidate is suitable for the position by carrying out various considerations so that later it will produce which of the candidates will occupy the position of head of the unit. So in this way it will require quite a long process and also in determining the criteria for each candidate is done manually so that the reports generated are not very accurate. With the application of Fuzzy Multiple Attribute Decision Making (FMADM) using the Simple Additive Weighting (SAW) method, the weight, criteria and ranking values of each Lecturer who are candidates for Head of Work Units are obtained. So that by calculating the Decision Support System to Determine Lecturer Candidates for the Head of Work Unit Positions at the Islamic University of Kuantan Singingi By Applying the Simple Additve Weighting (SAW) Method, it can help users determine Lecturer candidates for the position of head of work units at Kuantan Singingi Islamic University.